2010
DOI: 10.1590/s0366-69132010000100015
|View full text |Cite
|
Sign up to set email alerts
|

Cimento aluminoso e seus efeitos em concretos refratários magnesianos espinelizados in situ

Abstract: O uso de concretos refratários alumina-magnésia ligados por cimento aluminoso (CAC) apresenta vantagens decorrentes da presença de espinélio e de CA6 (CaO.6Al2O3), ambas formadas in-situ e acompanhadas de expansão. Estas fases possuem alta resistência a escórias básicas e ao choque térmico, propriedades estas imprescindíveis para aplicação em panelas siderúrgicas. Estudos anteriores mostraram que o teor de CAC utilizado em concretos alumina-magnésia influencia a expansão do material, principalmente devido à fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…These findings agreed well with what was found in [17]. The phases CA 6 , spinel, and gehlenite identified by XRD analysis indicated that the castables molded with the resin can display good resistance to the thermal shock [14,[16][17][18][19] as it is shown ahead. Fig.…”
Section: Resultssupporting
confidence: 87%
“…These findings agreed well with what was found in [17]. The phases CA 6 , spinel, and gehlenite identified by XRD analysis indicated that the castables molded with the resin can display good resistance to the thermal shock [14,[16][17][18][19] as it is shown ahead. Fig.…”
Section: Resultssupporting
confidence: 87%
“…These findings agreed well with what was found in [17]. The phases CA 6 , spinel, and gehlenite identified by XRD analysis indicated that the castables molded with the resin can display good resistance to the thermal shock [14,[16][17][18][19] as it is shown ahead.…”
Section: Castablesupporting
confidence: 87%